2009
DOI: 10.1002/jccs.200900051
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrophoretic Separation of Tricyclic Antidepressants Using 1‐Alkyl‐3‐Methylimidazolium‐Based Ionic Liquids as Background Electrolyte

Abstract: A capillary electrophoretic (CE) method coupled with the use of 1-ethyl-3-methylimidazolium tetrafluoroborate (1E-3MI-TFB) ionic liquid as background electrolyte (BGE) has been developed for the simultaneous separation of nine tricyclic antidepressants, viz. amitriptyline (Ami), clomipramine (Clo), desipramine (Des), fluphenazine (Flu), imipramine (Imi), nortriptyline (Nor), promazine (Pro), thioridazine (Thi) and trimipramine (Tri). Resolution of TCAs with similar molecular structures and pK a values was acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Moreover, the interaction between hydrogen at the C-2 carbon of the IL and the acid drugs played an important role in the separation. The same type of IL was selected for the enantiorecognition of nine tricyclic antidepressants in the study reported by Tsai et al [213] β-CD it allowed the resolutions of 3.8, 3.5, 2.8 and 2.5 for miconazole, econazole, ketoconazole and itraconazole, respectively, to be obtained.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…Moreover, the interaction between hydrogen at the C-2 carbon of the IL and the acid drugs played an important role in the separation. The same type of IL was selected for the enantiorecognition of nine tricyclic antidepressants in the study reported by Tsai et al [213] β-CD it allowed the resolutions of 3.8, 3.5, 2.8 and 2.5 for miconazole, econazole, ketoconazole and itraconazole, respectively, to be obtained.…”
Section: Capillary Electrophoresismentioning
confidence: 99%